Targeting in social programs : avoiding bad bets, removing bad apples - Schuck, Peter H.; Zeckhauser, Richard (Brookings Institution Press, 2006)
"Provides a framework for analyzing the challenges involved in defining bad bets and bad apples and discusses the safeguards that any classification process must provide. Examines public schools, public housing, and medical care and proposes policy changes that could reduce the problems these two groups pose in social welfare programs"--Provided by publisher
Keywords: Public welfare administration -- United States.; Human services -- Government policy -- United States.; United States -- Social policy -- 1993-; Aide sociale -- Administration -- États-Unis.; Services sociaux -- Politique gouvernementale -- États-Unis.; États-Unis -- Politique sociale -- 1993-; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare.; SOCIAL SCIENCE -- Human Services.; Human services -- Government policy; Public welfare administration; Social policy; United States; Since 1993